Emerging sustainable solutions for depollution: Geopolymers. (28th February 2019) - Asim, Nilofar; Alghoul, Mohammad; Mohammad, Masita; Amin, Mohamad Hassan; Akhtaruzzaman, M.; Amin, Nowshad; Sopian, Kamaruzzaman
Graphical abstract: Highlights: Catalyst geopolymers could utilize for the de-pollution of surrounding environment. Recent progress in substituting concrete & substrates with geopolymers is discussed. The review highlight studies used waste materials for catalyst geopolymer synthesis. Agricultural and industrial wastes have been identified as potential resources. Opportunities and Challenges remaining for a wider use are discussed. Abstract: Air pollution and water pollution are critical issues because they negatively affect ecosystem and human health, as well as affecting buildings and industries. Utilizing photocatalysts that rely on light irradiation to decompose pollutants is a promising solution to this issue. Geopolymers, when used as a green substitute for cement and other engineered materials, can be synthesized using different agricultural and industrial wastes. These materials exhibit synergies in the depollution process and can be regarded as cost effective and novel in the context of removing organic pollution from water and air to protect and improve the environment. Geopolymer catalytic performance is closely linked to the composition, microstructure, and preparation method of the geopolymer. This review investigates the types of geopolymers and catalysts and their corresponding preparation methods and performances. The limitations of these products and future works are also detailed.